This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Really thinking the unthinkable!
This solution is nice..
Nice solution
x 3 + 4 x = 8
x 3 = 8 − 4 x
Squaring both sides.
x 6 = 6 4 + 1 6 x 2 − 6 4 x
x 6 + 6 4 x = 1 6 x 2 + 6 4
From the given equation:
x 7 + 6 4 x 2 = x ( x 6 + 6 4 x )
x 7 + 6 4 x 2 = x ( 1 6 x 2 + 6 4 ) = 1 6 ( x 3 + 4 x )
1 6 ( 8 ) = 1 2 8
let's say dividend = x^7+64x^2 and divider = x^3+4x . Then you will find out by factor theorem that quotient is = x^4 - 4x^2 + 16 and remainder = 64x^2 - 64x . then you can write : x^7+64x^2 = (x^3+4x) (x^4-4x^2+16) + 64x^2-64x ; We know that x^3+4x = 8 ; x (x^2+4) = 8 ; also x = 8/(x^2+4) ; Then Ans = 8 (x^4-4x^2+16) + 64x^2-64x ; Write x^4 - 4x^2 + 16 as (x^2+4)^2 -12x^2 As you know x^2+4 = 8/x ; By doing some substitution like (8-x^3)/x = 4 and interpretation You will get Ans = 32 4 = 128
Problem Loading...
Note Loading...
Set Loading...
It is given that x 3 + 4 x = 8 .
Multiplied by x 4 : x 7 + 4 x 5 = 8 x 4
x 7 + 4 x 2 ( x 3 + 4 x − 4 x ) = 8 x ( x 3 + 4 x − 4 x )
x 7 + 4 x 2 ( 8 − 4 x ) = 8 x ( 8 − 4 x )
x 7 + 3 2 x 2 − 1 6 x 3 = 6 4 x − 3 2 x 2
x 7 + 3 2 x 2 − 1 6 ( 8 − 4 x ) = 6 4 x − 3 2 x 2
x 7 + 3 2 x 2 − 1 2 8 + 6 4 x = 6 4 x − 3 2 x 2
x 7 + 6 4 x 2 = 1 2 8